Tetrakis(4-aminopyridine-κN (1))dichloridocopper(II) monohydrate - Fun, Hoong-Kun (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, [CuCl(2)(C(5)H(6)N(2))(4)]·H(2)O, contains two crystallographically independent complex molecules and two water molecules. The Cu(II) ion in each molecule is six-coordinated in an elongated octahedral geometry, with the equatorial plane defined by four pyridine N atoms of four aminopyridine ligands and the axial positions occupied by two Cl atoms. In the crystal structure, molecules are linked into a three-dimensional framework by C—H⋯Cl, O—H⋯Cl, N—H⋯O, N—H⋯Cl and N—H⋯N hydrogen bonds and C/N—H⋯π interactions involving the pyridine rings.